2020
DOI: 10.30574/gscbps.2020.10.2.0018
|View full text |Cite
|
Sign up to set email alerts
|

The importance of nanotechnology and drug carrier systems in pharmacology

Abstract: Nanotechnology is one of the newest and most interesting areas of recent years. It offers innovations in diagnosis and treatment with the integration of limited size nanoparticles into larger living systems. It was found application in the field of microbiology, vaccine production, wound healing, tissue regeneration, and genetic, especially in pharmacology. It was significantly increased in the life quality of patients compared with traditional methods due to a number of superiorities such as demonstrated tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…to the targeted site. 18 NPs are beneficial when compared to conventional drugs because they improve the delivery of insoluble drugs, increase bioavailability, reduce side effects, and enhance treatment effectiveness. 17 Novel cartilage affinity peptide (CAP, DWRVIIPPRPSA) -modified nanoparticles (Gd 2 (CO 3 ) 3 @PDA-PEGDWpeptide) coated with polydopamine (PDA) were created by Ouyang and group that presented significant decrease in apoptosis and inflammation and increased maturation of chrondrocytes in vitro.…”
Section: Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…to the targeted site. 18 NPs are beneficial when compared to conventional drugs because they improve the delivery of insoluble drugs, increase bioavailability, reduce side effects, and enhance treatment effectiveness. 17 Novel cartilage affinity peptide (CAP, DWRVIIPPRPSA) -modified nanoparticles (Gd 2 (CO 3 ) 3 @PDA-PEGDWpeptide) coated with polydopamine (PDA) were created by Ouyang and group that presented significant decrease in apoptosis and inflammation and increased maturation of chrondrocytes in vitro.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Additionally, they can improve targeted drug delivery, elevate PK parameters, and regulate drug release at the injection site. [16][17][18][19][20][21][22][23][24] Kartogenin (KGN), a small molecule capable of enhancing chondrogenic differentiation of human mesenchymal stem cells (hMSCs), has shown promise in cartilage regeneration at the tendon-bone junction when injected directly into intact rat patellar tendons in vivo with negligible potential for systemic toxicity, evidenced by low concentrations of the molecule in the intra-articular space. 25,26 Zhang and group demonstrated that direct injection at wound site might not be the optimal mode of delivery as it is difficult to limit the KGN to its intended location without a scaffold.…”
Section: Dendrimersmentioning
confidence: 99%